Single-cell sequencing: a powerful technique to understand the pathophysiology of auditory disorders - Tuset, Maria-Pia; Wiefels, Matthew D.; McKenna, Keelin; Mittal, Jeenu; Gowda, Chirag; Mittal, Rahul; Eshraghi, Adrien A. (Frontiers in Audiology and Otology, 2023)
Deciphering the inner ear transcriptome has allowed major breakthroughs in therapeutic development for auditory disorders. Single-cell sequencing (SCS) technologies, through the analysis of cellular heterogeneity and the identification of novel gene markers, can significantly enhance our understanding about auditory disorders. The application of SCS has allowed the identification of gene targets specific to the inner ear cellular subtypes such as supporting cells, hair cells, stria vascularis cells and spiral ganglion neuron cells. SCS has provided new insights into the molecular mechanisms underlying the pathophysiology of auditory disorders such as noise-trauma induced hearing loss, ototoxicity, sudden sensorineural hearing loss (SSNHL), vestibular schwannomas and acute otitis media, leading to the discovery of novel therapeutic targets. The objective of this perspective article is to discuss recent advancements regarding the utilization of SCS for inner ear research. With global initiatives striving to overcome the increasing burden of hearing loss, the SCS technique holds a great potential in revolutionizing the management of auditory disorders, paving the way to develop effective treatment modalities.